2021
DOI: 10.1038/s41598-021-86699-w
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of treatment to improve gastrointestinal functions after colorectal surgery within enhanced recovery programmes: a systematic review and meta-analysis

Abstract: Despite a significant improvement with enhanced recovery programmes (ERP), gastro-intestinal (GI) functions that are impaired after colorectal resection and postoperative ileus (POI) remain a significant issue. In the literature, there is little evidence of the distinction between the treatment assessed within or outside ERP. The purpose was to evaluate the efficiency of treatments to reduce POI and improve GI function recovery within ERP. A search was performed in PubMed and Scopus on 20 September 2019. The s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 80 publications
(16 reference statements)
1
24
0
Order By: Relevance
“…With concomitant opioid treatment, alvimopan use may be associated with shorter times to tolerance of a soft diet, return of gastrointestinal function, and decreased LOS. However, no randomized clinical or cost-effectiveness trials have validated these findings in ERAS ® patients [ 58 , 59 , 60 , 61 ], and other safer, less costly agents exist, such as naloxegol and naldemedine [ 62 , 63 ]. Nevertheless, a 5-month retrospective pilot study to reduce alvimopan use after GI function recovery successfully eliminated over two-thirds of postoperative doses through pharmacist recommendation to discontinue [ 64 ].…”
Section: Resultsmentioning
confidence: 99%
“…With concomitant opioid treatment, alvimopan use may be associated with shorter times to tolerance of a soft diet, return of gastrointestinal function, and decreased LOS. However, no randomized clinical or cost-effectiveness trials have validated these findings in ERAS ® patients [ 58 , 59 , 60 , 61 ], and other safer, less costly agents exist, such as naloxegol and naldemedine [ 62 , 63 ]. Nevertheless, a 5-month retrospective pilot study to reduce alvimopan use after GI function recovery successfully eliminated over two-thirds of postoperative doses through pharmacist recommendation to discontinue [ 64 ].…”
Section: Resultsmentioning
confidence: 99%
“…Currently, the incidence of colorectal cancer is increasing, and most patients know little about postoperative recovery, which leads to a series of negative emotions after surgery. Several studies have shown that NOSES and postoperative rehabilitation treatment can promote the early recovery of patients ( 22 , 23 ). This study showed that the SAS and SDS scores and postoperative rehabilitation indexes of patients in the NOSES group were better than those in the LAP group.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of cesarean section, the impact of coffee on LOS after cesarean section may be small because the hospital stay is short to begin with [48,49]. In the case of colorectal surgery, coffee had a relatively weak effect on POI, which may be due to other factors related to POI, such as postoperative exercise and nutrition [35,50].…”
Section: Discussionmentioning
confidence: 99%